2020
DOI: 10.1186/s13047-020-00413-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to wearing therapeutic footwear among people with diabetes

Abstract: Aims: People at increased risk of developing diabetic foot ulcers often wear therapeutic footwear less frequently than is desirable. The aims were to identify patient groups prone to nonadherence to wearing therapeutic footwear and modifiable factors associated with adherence. Materials and methods: A questionnaire was mailed to 1230 people with diabetes who had been fitted with therapeutic footwear. Independent variables were categorized into five domains. For each domain, variables that were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…Group-TF&HoU ranked this factor third. The positive association between severity of the foot condition (Group-TF&HoU persons had poor foot health) and the importance of using TF is in line with previous literature [ 24 – 26 ]. The reason why this factor was not ranked in first place could be related to subjects’ underestimation of their actual foot health.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Group-TF&HoU ranked this factor third. The positive association between severity of the foot condition (Group-TF&HoU persons had poor foot health) and the importance of using TF is in line with previous literature [ 24 – 26 ]. The reason why this factor was not ranked in first place could be related to subjects’ underestimation of their actual foot health.…”
Section: Discussionsupporting
confidence: 90%
“…A possible solution might be to introduce regular motivational interviewing sessions instead of only once (with 2 45-minute sessions in 1 week). Other suggestions to increase the use of TF were given by Jarl et al [ 26 ]. Their suggestion was to eliminate the temptation to use non-TF and provide a reminder to use TF [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, studies have found these different offloading treatments offer different levels of desirable and undesirable effects and in turn produce different healing outcomes [ 9 , 10 , 11 ]. Additionally, studies have indicated that best practice offloading treatments have low rates of use; i.e., low prescription by clinicians [ 8 , 15 , 16 , 17 ] and low adherence by patients [ 18 , 19 , 20 , 21 , 22 , 23 ]. Further studies suggest there are many potential barriers and solutions to the use of these best practice offloading treatments [ 15 , 20 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have indicated that best practice offloading treatments have low rates of use; i.e., low prescription by clinicians [ 8 , 15 , 16 , 17 ] and low adherence by patients [ 18 , 19 , 20 , 21 , 22 , 23 ]. Further studies suggest there are many potential barriers and solutions to the use of these best practice offloading treatments [ 15 , 20 , 21 , 24 ]. Thus, the aims of this paper were to review the best available evidence firstly on the effects of offloading treatments to heal people with DFU, secondly on the use of offloading treatments in clinical practice, thirdly on the common barriers and solutions to using these offloading treatments, and lastly discuss promising emerging solutions that may improve offloading treatments in future.…”
Section: Introductionmentioning
confidence: 99%
“…According to Collings et al (2019) [40] and Jarls et al (2020) [41], therapeutic / suitable footwear is often used to reduce high tissue pressures associated with the risk of foot ulceration, therefore, guidelines for the care of the feet of people with diabetes recommend the use of therapeutic shoes or personalized insoles in the preventive management of people at risk of foot ulceration, as de ned by the National Institute for Health and Care Excellence [38].…”
Section: Discussionmentioning
confidence: 99%